2003
DOI: 10.1161/01.cir.0000079164.95019.5a
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Cardiac Procedures and Mortality Among Long-Term Survivors of Cardiac Arrest

Abstract: Background-It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 26 publications
5
51
2
1
Order By: Relevance
“…In our study, IHCA rates were higher in regions with a greater proportion of nonwhite patients, which may reflect racial disparities in the quality of inpatient care, as reported in several studies. 35,36 Furthermore, a higher proportion of hospitals in the West were medium sized and in urban locations compared with the Midwest (Table 1). Hospital size may be an indirect marker of available resources, with larger hospitals having more resources in place for the early recognition of clinical deterioration and prevention of IHCA.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, IHCA rates were higher in regions with a greater proportion of nonwhite patients, which may reflect racial disparities in the quality of inpatient care, as reported in several studies. 35,36 Furthermore, a higher proportion of hospitals in the West were medium sized and in urban locations compared with the Midwest (Table 1). Hospital size may be an indirect marker of available resources, with larger hospitals having more resources in place for the early recognition of clinical deterioration and prevention of IHCA.…”
Section: Discussionmentioning
confidence: 99%
“…1 Much of the evidence about disparities concerns cardiac care, showing that minorities receive lower quality care from lower quality cardiac surgeons 2 and have worse outcomes than Whites. 1,3,4 Controlling for clinical characteristics, Blacks are less likely to be referred for cardiac catheterization, 1 less likely to receive reperfusion therapy, 5 percutaneous transluminal coronary angioplasty (PTCA), 6 and coronary artery bypass graft (CABG) than Whites. 3,6,7 Blacks and other minorities have more limited access to new technologies, with larger disparities in utilization rates compared with Whites when a technology is new, a disparity that diminishes (but does not disappear) as the technology diffuses into regular care.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Compared with white patients, minority patients are found to be treated at hospitals with lower adherence to composite quality measures, and thus are less likely to receive evidence-based care. 8 -10 It is suggested that quality improvement programs can enhance a hospital's adherence to practice guidelines and patients' outcomes.…”
mentioning
confidence: 99%